Cellular and Genomic Properties of Haloferax gibbonsii LR2-5, the Host of Euryarchaeal Virus HFTV1 - Tittes, Colin; Schwarzer, Sabine; Pfeiffer, Friedhelm; Dyall-Smith, Mike; Rodriguez-Franco, Marta; Oksanen, Hanna M.; Quax, Tessa E. F. (Frontiers in Microbiology, 2021)
Hypersaline environments are the source of many viruses infecting different species of halophilic euryarchaea. Information on infection mechanisms of archaeal viruses is scarce, due to the lack of genetically accessible virus-host models. Recently a new archaeal siphovirus, Haloferax tailed virus 1 (HFTV1), was isolated together with its host belonging to the genus Haloferax, but it is not infectious on the widely used model euryarcheon Hfx. volcanii. To gain more insight into the biology of HFTV1 host strain LR2-5, we studied characteristics that might play a role in its virus susceptibility: growth-dependent motility, surface layer, filamentous surface structures and cell shape. Its genome sequence showed that LR2-5 is a new strain of Hfx. gibbonsii. LR2-5 lacks obvious viral defense systems, such as CRISPR-Cas, and the composition of its cell surface is different from Hfx. volcanii, which might explain the different viral host range. This work provides first deep insights into the relationship between the host of halovirus HFTV1 and other members of the genus Haloferax. Given the close relationship to the genetically accessible Hfx. volcanii, LR2-5 has high potential as a new model for virus-host studies in euryarchaea.